2020
DOI: 10.17759/jmfp.2020090401
|View full text |Cite
|
Sign up to set email alerts
|

Media multitasking: from cognitive functions to digital

Abstract: The article presents the phenomenon of multitasking, representing simultaneous execution of two or more mental operations. Its particular type, media multitasking (MMT), is also considered as a relatively new format for combining various information flows that meets the requirements of the digital environment. The historical perspective of studying multitasking is presented: from individual experiments on the selectivity of attention to the phenomenon of digital everyday life. Modern empirical studies of MMT c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…e regulatory component of metacognition is important in learning, as a result of which resources are allocated and concentration on meaningful tasks is achieved. e regulatory component of metacognition may be related to MMT (Soldatova et al, 2020b). In a study by Terry and colleagues (2016), it was found that students with higher metacognition preferred to multitask less, which may identify the self-regulatory nature of multitasking.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…e regulatory component of metacognition is important in learning, as a result of which resources are allocated and concentration on meaningful tasks is achieved. e regulatory component of metacognition may be related to MMT (Soldatova et al, 2020b). In a study by Terry and colleagues (2016), it was found that students with higher metacognition preferred to multitask less, which may identify the self-regulatory nature of multitasking.…”
Section: Introductionmentioning
confidence: 99%
“…MMT is de ned as an activity format that involves performing multiple tasks simultaneously using digital devices. Among the approaches to the study of MMT are the successive and simultaneous approaches (Soldatova et al, 2020b). MMT is also studied as digital distraction (Aagaard, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, students show worse understanding and memorization of the material. [9][10][11] This brief overview allows to draw several conclusions. First, the scientists focus primarily on the peers of the Internet (from children to adolescents).…”
Section: Introductionmentioning
confidence: 99%